Fitness Trainers’ Physical Attractiveness and Gym Goers’ Exercise Intention - Soekmawati; Robert Jeyakumar Nathan; Pei-Kian Tan; Vijay Victor (International Journal of Business and Society, 2022)
In line with the law of attraction, physical attractiveness has been widely used in marketing as well as advertising due to its potency in persuading consumers to take action. However, would physical attractiveness of a fitness trainer influence gym goers’ intention to exercise? This question motivated this research. Based on recent literature reviews, several research constructs were identified to form a research framework to investigate the physical attractiveness phenomena in the fitness industry. Hypothetically, the impact of the physical attractiveness of a fitness trainer on gym goers’ exercise intention is postulated to be mediated by trainer’s perceived expertise, trustworthiness, likeability and perceived health. Questionnaires were administered among gym-goers from 10 randomly selected fitness centres across three districts of Melaka State in Malaysia, and 192 final sample data were obtained. Data analysis reveals fitness trainer’s perceived expertise and likeability significantly mediates the relationship between the physical attractiveness of fitness trainers and gym goers’ exercise intention. Physical attractiveness of fitness trainers does impact the exercise intention of gym goers indirectly. Implications of the findings to theory and practice are also discussed in this paper, as well as suggestions for future studies.